2009
DOI: 10.1002/anie.200801987
|View full text |Cite
|
Sign up to set email alerts
|

Acetylides from Alkyl Propiolates as Building Blocks for C3 Homologation

Abstract: Three that matter: Metal acetylides from alkyl propiolates allow C3 homologations with transference of their versatile reactivity profile to products that can then react without further elaboration. Metal‐free acetylides, which are generated by the action of a good nucleophile on the alkyl propiolate, react with suitable electrophiles through different domino reactions to generate skeletal diversity. Alkyl propiolates are reagents with a versatile reactivity profile that entirely remains in the C3‐homologate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 82 publications
3
33
0
Order By: Relevance
“…This result might be explained by ligand exchange of Cr II , allowing nucleophilic substitution of labile ligands (e.g., Cl) to give nucleophilic chromium(II) acetylide 15 . Indeed, like Zn II , Cu I , or Au I acetylides that are generated in situ from terminal alkynes at room temperature upon treatment with an organic base (TEA, i Pr 2 N n Pr, or NH 4 OH) [13,15c,15d,29] by ligand exchange, this substitution reaction occurs for Cr II . This mechanism is supported by kinetic studies reported by Merbach, who showed that this ligand exchange is kinetically very fast and favored for Cr II , whereas Cr III is known to be extremely resistant to this process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result might be explained by ligand exchange of Cr II , allowing nucleophilic substitution of labile ligands (e.g., Cl) to give nucleophilic chromium(II) acetylide 15 . Indeed, like Zn II , Cu I , or Au I acetylides that are generated in situ from terminal alkynes at room temperature upon treatment with an organic base (TEA, i Pr 2 N n Pr, or NH 4 OH) [13,15c,15d,29] by ligand exchange, this substitution reaction occurs for Cr II . This mechanism is supported by kinetic studies reported by Merbach, who showed that this ligand exchange is kinetically very fast and favored for Cr II , whereas Cr III is known to be extremely resistant to this process.…”
Section: Resultsmentioning
confidence: 99%
“…[13] Classical methods have mainly exploited the relatively high acidity of terminal acetylenic C–H bonds to form metal alkynylides, either by direct metalation using strong bases, such as n -butyllithium or lithium diisopropylamide at low temperature (−100 to −80 °C), [14] or upon treatment with tertiary amines in the presence of a stoichiometric or catalytic amount of the metal salt of interest (Figure 1, route a). [15] Lithium and silver acetylides prepared by this approach are also utilized for the preparation of other acetylides by transmetalation with magnesium, zinc, cerium, and other metals (Figure 1, route b).…”
Section: Introductionmentioning
confidence: 99%
“…Propargylic alcohol derivatives are versatile precursors to many organic compounds and have extensive applications in organic synthesis . For example, in 2010, Fukuyama, Ryu, Fensterbank, and Malacria developed the Rh I ‐catalyzed reaction of propargylic acetate 1 (R 1 = H) with CO to generate phenol derivative 2 (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…The main concerns rely on their stepwise character,t heir difficulty for scalingu pa nd the use of elaborated reactants and/or toxic cyanide reagents.T herefore, the hydrocyanation of activated terminal alkynes remains an unresolved challenge in preparative synthetic chemistry,e ven in spite of the synthetic [8] and pharmaceutical [9] importance of the resulting 3-substituted acrylonitriles.H ydrocyanationp rotocols aimed to cover this gap with real-worldp reparative value should meet three main conditions for:1 )sustainability:t hey should be catalytic and scalable;2 )safety:t he use or generation of toxic HCN should be avoided and 3) practicality: they should be universal,o perationally simple,e fficient and economic.W ith these principles as ag uide, we have designedt he catalytic manifold depicted in Scheme 2. The manifold is based on the reactivity generation principle "a good nucleophile generates as trong base", [10] andi tu ses an activated terminal alkyne as substrate, acetonec yanohydrin [11] as the cyanide source [5d] and 1,4-diazabicyclo[2.2.2]octane (DABCO) as the nucleophilic catalyst. [12] The catalytic cyclei si nitiated by the addition of DABCO ontot he terminal alkyne to generate the zwitterion I,w hich should deprotonatet he acetonec yanohydrint o generate the ammonium acrylate II and ac atalytic amount of cyanidei on.…”
mentioning
confidence: 99%